Analisis Implementasi Nilai-Nilai Pancasila Bagi Generasi Muda Dalam Menghadapi Era Globalisasi Sebagai Perwujudan Jiwa Nasionalisme - Feronica Simanjorang; Adinda Eloyfani Ginting; Bella Amanda; Elhot Nicolas R Sianturi; Michael Gerald Simbolon; Hania Syakira (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In the midst of the onslaught of global culture, nationalism is a fundamental issue. To awaken the spirit of nationalism in the younger generation, it is necessary to instill exemplary values. This is very important because, without being based on a sense of nationalism, the spirit to work, unite, and achieve the goals of developing the country will never be achieved. This research uses literature study research methods. A sense of nationalism is very important for Indonesia's young generation to be able to become an advanced nation, a modern nation, a safe, peaceful, just and prosperous nation in the midst of globalization which is increasingly challenging the Indonesian state. As a nation and state among other nations in the world, it requires a high identity of nationalism from its citizens, especially among the younger generation of Indonesia. The spirit of nationalism is still needed by the existence of the Indonesian nation and state. High nationalism from citizens or the younger generation will make positive and best behavior for the nation and state. In the current era of globalization there are several tendencies to diminish the spirit of nationalism among the younger generation. This can be seen from a number of benchmarks, namely the lack of appreciation of the younger generation for native Indonesian culture, patterns and lifestyles of westernized youth, and so on. To overcome this problem, it is necessary to have an intensive and continuous movement in the world of education related to instilling a sense of nationalism in students from elementary to tertiary levels which must be carried out by teachers and lecturers in a way that respects and is proud of the original Indonesian culture.